Pharmaceutical Ethics - Wells, F. (Journal of medical ethics, 2004)
Edited by S Salek, A Elgar. John Wiley & Sons, 2002, £45.00, pp 210. ISBN 0471490571 Make no mistake, this interesting book emphatically reflects the backgrounds of its editors, as is to be expected, which are in pharmacy and in academic ethics. There is nothing wrong with that so long as we know. The stated target audience for the book are, however, those working in the clinical research of pharmaceutical products. Also it claims to cover a neglected area of medical ethics. What a pity therefore that the book pays no regard whatsoever to the report of the Faculty of Pharmaceutical Medicine on ethics in pharmaceutical medicine, first adopted and then published in 1997.1 Having said that, the editors’ preface refers to the issues which the research pharmacist may confront, as both a scientist and a member of society, and for this particular group of professionals the book will be of the greatest interest. Any collection of chapters or, as the editors prefer, articles, are likely to include those which are very good indeed and those which are more limited in their usefulness and appeal. Stimulation and thought provocation are the hallmarks of a valuable article, while irritation is the response to be most vigorously avoided. I must say that certain contributions within …